Intersecting Liabilities: A Critical Analysis of Criminal Accomplice Provisions in Employment Law Violations - Febrina, Mirani; Fatmawati, Nynda (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
Violations of the Regency/Municipal Minimum Wage (UMK) in Indonesia not only undermine workers’ fundamental rights but also expose structural deficiencies in the enforcement of labor criminal law. Previous studies have predominantly framed minimum wage violations as individual misconduct, thereby neglecting the systemic and collective dimensions of corporate decision-making. This article addresses that gap by critically examining the application of participation doctrines under Articles 55 and 56 of the Indonesian Penal Code (KUHP) and their relevance for attributing liability to actors across organizational hierarchies. Employing a normative juridical method with statutory and conceptual approaches, this study integrates doctrinal analysis, judicial interpretation, and comparative insights from global practices on corporate and collective criminal liability. The findings reveal that wage violations often result from deliberate policies formulated at managerial or corporate levels, thus requiring recognition of functional perpetration and structural participation. Furthermore, this article argues that the doctrine of abuse of circumstances (misbruik van omstandigheden) should be considered to exempt coerced or vulnerable actors from liability, thereby preventing the criminalization of structural victims. By advancing a critical interpretation of participation in labor-related crimes, this study contributes both to the theoretical development of collective liability in Indonesian criminal law and to practical reform strategies that strengthen the protection of workers’ constitutional rights.